Fast in-situ imaging method using non-axial scanning confocal Raman microscope. (August 2023) - Li, Rongji; Li, Angze; Su, Yunhao; Qiu, Lirong; Zhao, Weiqian
Highlights: Achieves non-axial scan focusing with large-scale and high-precision. In situ topographic imaging and Raman mapping ability under homologous excitation. A novel alternative approach with a higher speed level than the conventional method. Applied directly to existing confocal Raman microscopy. Abstract: Confocal Raman microscopy (CRM) is extensively employed in numerous fields because it provides molecular fingerprint information without destroying or labeling samples. For samples with large topographic fluctuations, existing technology requires axial scanning to achieve axial focusing, which further increases the time required for Raman mapping. Herein, a method called non-axial scanning confocal Raman microscopy (NASCRM), which constructs an axial focusing system with a large range and high precision by modifying the wide-field imaging system, is proposed. The axial focusing system combined with CRM can simultaneously realize in situ high-precision topography imaging and Raman mapping. Theoretical analyses and preliminary experiments reveal that the axial focusing resolution of NASCRM is approximately 3 nm and the sensing range is approximately 60 μm. Compared with CRM using confocal microscopy (CM) focusing (CM-CRM), the speeds within sensing range for axial focusing and Raman mapping are improved by 5.3 and 2.9 times, respectively. This study provides a novel method for both conventional CRM and CRM-based imaging in various fields.